Interdependent YpsA- and YfhS-Mediated Cell Division and Cell Size Phenotypes in Bacillus subtilis - Robert S. Brzozowski (American Society for Microbiology, 2020)
ABSTRACT Although many bacterial cell division factors have been uncovered over the years, evidence from recent studies points to the existence of yet-to-be-discovered factors involved in cell division regulation. Thus, it is important to identify factors and conditions that regulate cell division to obtain a better understanding of this fundamental biological process. We recently reported that in the Gram-positive organisms Bacillus subtilis and Staphylococcus aureus, increased production of YpsA resulted in cell division inhibition. In this study, we isolated spontaneous suppressor mutations to uncover critical residues of YpsA and the pathways through which YpsA may exert its function. Using this technique, we were able to isolate four unique intragenic suppressor mutations in ypsA (E55D, P79L, R111P, and G132E) that rendered the mutated YpsA nontoxic upon overproduction. We also isolated an extragenic suppressor mutation in yfhS, a gene that encodes a protein of unknown function. Subsequent analysis confirmed that cells lacking yfhS were unable to undergo filamentation in response to YpsA overproduction. We also serendipitously discovered that YfhS may play a role in cell size regulation. Finally, we provide evidence showing a mechanistic link between YpsA and YfhS. IMPORTANCE Bacillus subtilis is a rod-shaped Gram-positive model organism. The factors fundamental to the maintenance of cell shape and cell division are of major interest. We show that increased expression of ypsA results in cell division inhibition and impairment of colony formation on solid medium. Colonies that do arise possess compensatory suppressor mutations. We have isolated multiple intragenic (within ypsA) mutants and an extragenic suppressor mutant. Further analysis of the extragenic suppressor mutation led to a protein of unknown function, YfhS, which appears to play a role in regulating cell size. In addition to confirming that the cell division phenotype associated with YpsA is disrupted in a yfhS-null strain, we also discovered that the cell size phenotype of the yfhS knockout mutant is abolished in a strain that also lacks ypsA. This highlights a potential mechanistic link between these two proteins; however, the underlying molecular mechanism remains to be elucidated.